2014
DOI: 10.1007/s10620-014-3474-y
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Regulates Trypsin Activation, Inflammation, and Tissue Damage in Acute Pancreatitis in Mice

Abstract: Our findings show that HDAC regulates trypsin activation, inflammation, and tissue damage in AP. Thus, targeting HDAC could serve as novel therapeutic approach in the management of severe AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…We found that, differently to what was observed upon pan-HDAC inhibitor treatment (Hartman et al, 2015), MS-275 neither prevented the initial acinar damage nor the expression of chemokines necessary to recruit leukocytes. However, the inhibitor could diminish the recruitment of leukocyte populations, including macrophages and T cells sub-populations into the pancreas.…”
Section: Ms-275 and Pancreatic Inflammationcontrasting
confidence: 91%
See 1 more Smart Citation
“…We found that, differently to what was observed upon pan-HDAC inhibitor treatment (Hartman et al, 2015), MS-275 neither prevented the initial acinar damage nor the expression of chemokines necessary to recruit leukocytes. However, the inhibitor could diminish the recruitment of leukocyte populations, including macrophages and T cells sub-populations into the pancreas.…”
Section: Ms-275 and Pancreatic Inflammationcontrasting
confidence: 91%
“…Based on these observations, we hypothesize that HDAC activity may be a key factor in modulating not only leukocyte infiltration in the injured tissue but also gene expression changes in acinar cells affecting pancreatic regeneration. In support of this hypothesis, two recent studies showed that in vivo treatment with the pan-HDAC inhibitors sodium butyrate and trichostatin A (TSA), which target both class I and class II HDAC subfamilies, alleviated pancreatic damage, inflammation and fibrosis following L-arginine- (Kanika et al, 2015) or taurocholic acid-induced pancreatitis (Hartman et al, 2015) in rodents. However, in another study treatment with valproic acid had a detrimental effect on cerulein-induced pancreatitis, consequently delaying tissue recovery and reducing acinar cell proliferation (Eisses et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…This is very important as recently published data from Hartman et al showed that inhibition of HDAC decreased markers of pancreatitis and protected from tissue injury of the pancreas in C57Bl/6 mice subjected to taurocholic acid model of pancreatitis. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Of the 1976 cases of severe acute pancreatitis admitted to the 15 medical centers in China between 1990 and 2005, 25.2% were idiopathic [4]. 19.8% of the 337 patients with severe acute pancreatitis in Peking Union Medical College Hospital were idiopathic [4]. With the development of research and the progress of detection technology, the causes of some of idiopathic severe acute pancreatitis can be identified, such as small stone disease, Audi sphincter dysfunction and others [9].…”
Section: Idiopathicmentioning
confidence: 99%